Kecenderungan Narsistik Sebagai Mekanisme Pertahanan Psikologis: Efek Kesepian dan Pola Asuh Permisif pada Dewasa Awal - Ul Alimah, Afina Annisa; Yunida, Gina Sofia; Rahimah, Ainun Gina; Sabila, Ahda; Ilahiya, Salma Nur; Yuniarrahmah, Emma (Universitas Negeri Makassar, 2025)
Personality disorders are often found in society in various forms of behavior, one of which is narcissistic personality disorder (NPD). The main purpose of this research is to find out whether a role of loneliness and permissive parenting on narcissistic tendencies in early adulthood. This research uses quantitative approach with cross sectional study survey technique on 183 early adult around 18–27 years old (M = 17,61) in several regions of Indonesia. This research uses purposive sampling as sampling technique and the data is collected through Narcissistic Admiration and Rivalry Questionnaire (NARQ), UCLA Loneliness Scale Version 3, and Parental Authority Questionnaire (PAQ), which were carried out online by distributing instruments in the form of google forms. Data is analyzed using multiple regression. The result shows that (1) simultaneously loneliness and permissive parenting influence the emergence of narcissistic personality disorder tendencies in early adulthood, (2) partially loneliness is unable to influence the emergence of narcissistic personality disorder tendencies in early adulthood, and (3) partially permissive parenting influences the tendency of narcissistic personality disorder in early adulthood. Results of this study are expected to be a reference for creating educational programs on positive parenting patterns to minimize the emergence of narcissistic personality disorders.